Retrospective analysis of 1539 nasopharyngeal carcinoma cases: chemotherapy should not be excluded for non-Asian patients with T1-2N1M0 stage - Xin-Yu Li; Chang-Ying Zhong; Hui-Xian Xu (Frontiers in Oncology)
BackgroundMany results suggested that chemotherapy cannot provide survival benefit for stage II nasopharyngeal carcinoma. It remained unclear whether the efficacy of chemotherapy differed in non-Asian populations.ObjectiveIt was designed to analyze the effect of chemotherapy for Asian and non-Asian patients with stage II nasopharyngeal carcinoma.MethodPatients were collected using the SEER program. The variables included age, sex, race, marital status, survival time, survival status, TNM stage, radiation and chemotherapy. Utilizing the Rstudio (version: 2024.4.1.748) and R (version: 4.4.1), backward elimination method was employed to screen the variables and multivariate Cox regression analyses was conducted on the screened variables. Kaplan-Meier method was utilized to analyze the survival of sub-stages and different races with T1-2N1M0 stage. The log-rank test was used for statistical analysis.Result1539 patients were collected. Chemotherapy was statistically significant, with a hazard ratio (HR) of 0.64, P=0.003 in stage II patients. The HR for radiation was 0.33, P<0.001. Chemotherapy didn’t improve cancer-specific survival for patients with T2N0M0 stage. Asian and non-Asian races showed no difference in cancer-specific survival in T2N0M0 stage with HR of 1.85, P=0.13. For patients with T1-2N1M0 stage, chemotherapy improved cancer-specific survival with a HR of 0.53, P<0.001. No significant difference was in the Kaplan-Meier analysis between the two sub-stages (P=0.065). In T1-2N1M0 stage, multivariate Cox regression analysis for Asian race indicated that chemotherapy didn’t improve cancer-specific survival with a HR of 0.64, P=0.190. For non-Asian race, chemotherapy was found to improve cancer-specific survival, with a HR of 0.51, P<0.001. The Kaplan-Meier analysis of Asian and non-Asian patients with T1-2N1M0 stage exhibited significant differences (P<0.0001).ConclusionChemotherapy is correlated with the cancer-specific survival in non-Asian patients with T1-2N1M0-stage nasopharyngeal carcinoma, but not in Asian patients at the same stage. For patients with the T2N0M0 stage, chemotherapy is not correlated with the cancer-specific survival rate, regardless of ethnicity.